Nigeria and the Sustainable Development Goals: Why the Indigenous Languages Count - Okwudili, Ugwu, Eucharia; Opeyemi, Ogunremi, Patience (European Scientific Journal, ESJ, 2019)
Language as a tool for logical thinking and planning is unavoidable in every developmental effort. Nigeria is among the countries that were not able to achieve the Millennium Development Goals (MDGs). Among the reasons given for Nigeria’s low performance level was communication barrier. To achieve the Sustainable Development Goals (SDGs), the government has planned a transition strategy and hopes that it would be people-centred. Hence, she hopes to leave no Nigerian behind. As a multilingual nation, many Nigerians cannot function in English language but rely only on their various indigenous languages. Accommodating them in the SDG plans would require communicating with them in the languages that they understand. This could enhance collaboration and minimise a repeat of the previous failure. Unfortunately, there is no language plan in the government’s transition strategy. If development is about helping people to help themselves, then there must be collaboration among the planners of the SDGs and those for whom it is planned. But collaboration is only possible where there is a free flow of information. This paper is an attempt to reposition the indigenous languages at the hearts of all effort to achieve the 2030 agenda in Nigeria.